A New Species of Cyperus from India - Sahni, K. C.; Naithani, H. B. (Indian Forester, 1976)
A new species or Cyperus Linn., C. dwarkensis Sahni and Naithani from Gujarat is described. Allied to C. pannonicus. Differs in having 2 involucral bracts, stamens 1-2, style absent or very short, nut 1 Ã— 0.5 mm. In C. pannonicus. involucral bracts are 3, styles long, and nut 2 mm in diameter.